أنواع الماء في القرآن الكريم ودلالاتها العلمية Water Types in the Qur’an and their Scientific Implications - جاسم ليث سعود; الجدي فاتن محمد (Journal of Islam in Asia (E-ISSN 2289-8077), 2015)
الملخّص إن أهمية الماء ودوره في وجود واستمرار الحياة على الأرض، قد أغرى كثيراً من العلماء لإجراء التجارب والأبحاث العلمية للكشف عن مكونات الماء وأسراره ومصادر وروده، وعلى الرغم من كثرة البحوث العلمية التي قامت على الماء ودورته في الطبيعة، ووجوه الإعجاز العلمي للآيات القرآنية التي تحدثت عنه، إلا أن الألفاظ القرآنية لا يزال في محتواها الشيء الكثير من الناحية اللغوية والدلالية، فقد يحوي اللفظ القرآني الواحد أكثر من معنى، ويتحمل في سياقه دلالات إضافية، تجعل منه منجماً لحقائق علمية كشف عنها العلم الحديث بآلياته المتطورة في البحث. يهدف البحث إلى إبراز دقة وجزالة وغنى اللفظ القرآني، وإعجازه البلاغي، ثم ربط دلالات الألفاظ القرآنية المنطوقة والمفهومة، بما تم اكتشافه في البحوث العلمية الحديثة، فيما يتعلق بأنواع الماء المذكورة في القرآن الكريم تحديداً، وفي ذلك ما فيه من الآيات البينات على أن القرآن الكريم وحي إلهي، وليس من قول البشر، كما أنه محفوظ بحفظ الله تعالى له من التبديل والتحريف. واتبع فيه منهج التفسير الموضوعي التحليلي الذي يقضي بجمع كل الآيات المتعلقة بالموضوع، ووضعها على مائدة البحث العلمي، واستعراض أقوال العلماء القدامى والمحدثين في هذه المسألة، ومناقشتها والترجيح بينها؛ للخروج بمعرفة شمولية حول ما جاء في القرآن الكريم بهذا الخصوص، واستنتاج علاقات رابطة بين هذه الآيات، قد تؤدي للكشف عن المزيد من أسرار هذا الكتاب المعجز. الكلمات المفتاحية: أنواع الماء، القرآن الكريم، دلالاتها العلمية، العلماء، البشر. Abstract In view of the importance of water and its role in the existence and continuation of life on Earth, many scientists have conducted experiments and scientific research to detect the components of water, and its secrets and sources. In spite of the large number of scientific research conducted on water and its nature, in addition to the various scientific miracles of the Qur’anic verses that talked about, the linguistic and semantic point of view of the Qur’anic address on the issue of water with its many indications has gone largely overlooked. This paper argues that the semantic and linguistic details of the Qur’anic address can assist the research of modern science in this field. The research highlights the accuracy, abundance, and richness of the Qur’anic language in what concerns the types of water, and associates its semantic meanings with modern scientific research and discoveries. This presents evidence that the Holy Qur’an is divine revelation and not the words of man, and that it is divinely preserved from change and distortion. This study adopts the objective interpretation and analytical methods of Qur’anic exegesis by collecting all the verses on the subject whilst also reviewing the views of classical and contemporary scholars on this issue. From here, we hope to offer a comprehensive understanding of what is stated in the Qur’an in this regard, whilst also establishing concrete link between these verses, which may lead to detecting more of the secrets of this miraculous book. Key words: Water Types, the Qur’an, Scientific Implications, Scientists, Humans.